Teicoplanin – Tigecycline Combination Shows Synergy Against Mycobacterium abscessus - Aziz, Dinah B.; Teo, Jeanette W. P.; Dartois, Véronique; Dick, Thomas (Frontiers in Microbiology, 2018)
Lung disease caused by non-tuberculous mycobacteria (NTM), relatives of Mycobacterium tuberculosis, is increasing. Mycobacterium abscessus is the most prevalent rapid growing NTM. This environmental pathogen is intrinsically resistant to most commonly used antibiotics, including anti-tuberculosis drugs. Current therapies take years to achieve cure, if cure if achieved. Thus, there is an urgent medical need to identify new, more efficacious treatments. Here, we explore the possibility of repurposing antibiotics developed for other indications. We asked whether novel two-drug combinations of clinically used antibiotics can be identified that show synergistic activity against this mycobacterium. An in vitro checkerboard titration assay was employed to test 180 dual combinations of 41 drugs against the clinical isolate M. abscessus Bamboo. The most attractive novel combination was further profiled against reference strains representing three sub-species (M. abscessus subspec. abscessus, massiliense and bolletii) and a collection of clinical isolates. This resulted in the identification of a novel synergistic antibiotic pair active against the M. abscessus complex: the glycopeptide teicoplanin with the glycylcycline tigecycline showed inhibitory activity at 2-3 µM (teicoplanin) and 1-2 µM (tigecycline). This novel combination can now be tested in M. abscessus animal models of infection and / or patients.